ESTRUTURA E DINÂMICA DO FUNCIONAMENTO PSÍQUICO DE HOMENS ENVOLVIDOS EM VIOLÊNCIA DOMÉSTICA - Hokama, Erica (2015)
Violence of any kind and nature, is a phenomenon that happens since the beginning. The World Health Organization defines violence as the intentional use of physical force or power, real or threatened, against oneself, against another person, against a group or community, which can result in death, injury, psychological damage, problems of development or privation. Domestic violence is defined by the APA (2007) as any action that causes physical injury to one or more members of your family unit and can occur from a generation conflict (against children) and gender (violence against women) by setting up a physical assault, sexual abuse, psychological abuse, neglect within the family, perpetrated by an aggressor in superiority conditions (physical, age, social, psychological and / or hierarchical). This research aims to investigate the structure and dynamics of Psychic Functioning of Men Involved in Domestic Violence. We used the qualitative method, with four men in domestic violence situations. We used the qualitative method, with four men in domestic violence situations. As form of data collection was used an interview and Test of Object Relations (TRO) Phillipson. When analyzing the results, it can be observed that the fragile ego fears loneliness, the loss situations, and destructive attacks of the id and the permissive superego not contain them, and to support the persecutory attacks of objects, and depending on the paranoid and persecutory guilt the ego uses massive projective identification and idealization to hedge its destructiveness, staying in the paranoid-schizoid position. We conclude that the analysis of the structure and psychic dynamics and psychological treatment (individual or group) of men involved in domestic violence, together with other legal and social measures are necessary actions, therefore, can be a way of help- them cope with their limitations, deal with their anxieties, understand and control impulses, review and understand their beliefs and work your self-esteem. Starting from the assumption that domestic violence occurs in the relationship between men and women, treatment and understanding of the psychological aspects of men involved in domestic violence are extremely important to minimize this phenomenon, and should be combined with those already addressed to women.